Liquid Crystals: From Modified Phases to Applications 2014 (2014)
Liquid crystals are a state of matter which most of the population is aware of through its application in low power, flat panel displays, ranging from simple pocket calculator displays, via their mobile phones and tablets, all the way to the sophisticated screens on lap tops and televisions. Much less so are people aware of the fact that they are surrounded by liquid crystals in the form of washing detergents or cell membranes and the like. Liquid crystal research is a well established field, which started far more than a century ago, mainly through the synthesis of shape-anisotropic molecules which formed partially ordered states through a process now known as self-assembly. It became a niche topic around the time of the middle of the last century, due to the lack of apparent applications, while solid state and semiconductor devices conquered the world. It was not until the beginning of the 70s, with the invention of the dynamic light scattering and twisted nematic displays, that liquid crystal research boomed. Today we are looking at a mature field of research, which nevertheless still develops rapidly with the discovery of novel phases, new electro-optic effects, hybrid materials like polymer dispersed and polymer stabilized liquid crystals, or liquid crystal – particle dispersions with added functionality. Liquid crystal research is a field of multidisciplinarity, which brings together physicists, chemists, biologists, and device engineers, experimentalists, theoreticians and computer simulation scientists.